ACCOUNTABILITY ANALYSIS OF PERSONS TRADE IN PERSONS THROUGH ONLINE PROSTITUTION - Riko Yulian Prima; Bambang Hartono (PRANATA HUKUM, 2023)
Abstract Human trafficking is the act of recruiting, transporting, harboring, sending, transferring or receiving a person by means of the threat of force, use of force, abduction, confinement, fraud, deception, abuse of power or a position of vulnerability, debt bondage or payment or benefit, so as to obtain the consent of another person. who has control over the other person, whether carried out within the country or between countries, for the purpose of exploitation or causing people to be exploited in accordance with Article 1 paragraph (1) of Law Number 21 of 2007 concerning Eradication of the Crime of Human trafficking. Article 2 paragraph (1) of Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Human trafficking explains that any person who recruits, transports, harbors, sends, transfers, or accepts someone with threats of violence, use of force, kidnapping, confinement, forgery, fraud, abuse of power or a position of vulnerability, debt bondage or giving payments or benefits despite obtaining the consent of a person who has control over another person, for the purpose of exploiting that person in the territory of the Republic of Indonesia. 15 (fifteen) years and a minimum fine of Rp. 120,000,000.00 (one hundred and twenty million rupiah) and a maximum of Rp. 600,000,000.00 (six hundred million rupiah). Keywords: Human Trafficking, Online Prostitution, Criminal Actors.